2014
DOI: 10.1002/2013pa002535
|View full text |Cite
|
Sign up to set email alerts
|

Nd isotopic structure of the Pacific Ocean 70–30 Ma and numerical evidence for vigorous ocean circulation and ocean heat transport in a greenhouse world

Abstract: The oceanic meridional overturning circulation (MOC) is a crucial component of the climate system, impacting heat and nutrient transport, and global carbon cycling. Past greenhouse climate intervals present a paradox because their weak equator-to-pole temperature gradients imply a weaker MOC, yet increased poleward oceanic heat transport appears to be required to maintain these weak gradients. To investigate the mode of MOC that operated during the early Cenozoic, we compare new Nd isotope data with Nd tracer-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
98
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 102 publications
(164 reference statements)
14
98
1
Order By: Relevance
“…Lacan et al, 2012) due to mixing, which is a similar magnitude to the offset observed in our data (∼ 1 ε Nd unit). Our interpretation of these δ 13 C and ε Nd data supports changes in areas of convection that are consistent with simulations of the PETM with coupled climate models (Lunt et al, 2012;Thomas et al, 2014) and with a comprehensive climate model (Winguth et al, 2010). It is impossible to interpret from the Nd isotope data alone whether there was reduced or increased overturning associated with carbon release, as these data reflect water mass geometries and not rates of overturning.…”
Section: A Conceptual Model To Explain the Recordssupporting
confidence: 77%
See 2 more Smart Citations
“…Lacan et al, 2012) due to mixing, which is a similar magnitude to the offset observed in our data (∼ 1 ε Nd unit). Our interpretation of these δ 13 C and ε Nd data supports changes in areas of convection that are consistent with simulations of the PETM with coupled climate models (Lunt et al, 2012;Thomas et al, 2014) and with a comprehensive climate model (Winguth et al, 2010). It is impossible to interpret from the Nd isotope data alone whether there was reduced or increased overturning associated with carbon release, as these data reflect water mass geometries and not rates of overturning.…”
Section: A Conceptual Model To Explain the Recordssupporting
confidence: 77%
“…Such data provide high-resolution records of changes in past deep-water mass mixing and are used to reconstruct deep-ocean circulation (Böhm et al, 2015;Martin et al, 2010Martin et al, , 2012Piotrowski et al, 2004Piotrowski et al, , 2005Piotrowski et al, , 2008Thomas et al, 2014). Here we compare deep-water Nd isotope data obtained from leachates to fish teeth records and carbon isotope data from the same cores, which allows us to elucidate the causes and controls of δ 13 C variations in the past deep oceans (Piotrowski et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nd tracer-enabled ocean simulations that are able to reproduce the observed pattern of Eocene Nd data have vigorous bipolar Pacific sinking, with southern rather than North Pacific bottom water dominating (Thomas et al, 2014). Furthermore, idealized GCM simulations show that salt advection feedbacks 20 create a competition between North Pacific and North Atlantic deep water formation (Wolfe and Cessi, 2014), so that the onset of North Atlantic sinking may imply a shutdown of North Pacific sinking and vice versa.…”
mentioning
confidence: 95%
“…The operating mode of the MOC was significantly different during the Late Cretaceous and early Paleogene (e.g., Thomas et al 2014). In the modern oceans, Antarctica is surrounded by the world's strongest ocean current, the Antarctic Counter Current (ACC), which flows around Antarctica and reaches from the surface to abyssal depths.…”
Section: Ocean Circulationmentioning
confidence: 99%